Dietary Insulin Load and Cancer Recurrence and Survival in Patients With Stage III Colon Cancer: Findings From CALGB 89803 (Alliance). (21st June 2018) - Morales-Oyarvide, Vicente; Yuan, Chen; Babic, Ana; Zhang, Sui; Niedzwiecki, Donna; Brand-Miller, Jennie C; Sampson-Kent, Laura; Ye, Xing; Li, Yanping; Saltz, Leonard B; Mayer, Robert J; Mowat, Rex B; et al.
Abstract: Background: Evidence suggests that diets inducing postprandial hyperinsulinemia may be associated with increased cancer-related mortality. The goal of this study was to assess the influence of postdiagnosis dietary insulin load and dietary insulin index on outcomes of stage III colon cancer patients. Methods: We conducted a prospective observational study of 1023 patients with resected stage III colon cancer enrolled in an adjuvant chemotherapy trial who reported dietary intake halfway through and six months after chemotherapy. We evaluated the association of dietary insulin load and dietary insulin index with cancer recurrence and survival using Cox proportional hazards regression adjusted for potential confounders; statistical tests were two-sided. Results: High dietary insulin load had a statistically significant association with worse disease-free survival (DFS), comparing the highest vs lowest quintile (adjusted hazard ratio [HR] = 2.77, 95% confidence interval [CI] = 1.90 to 4.02, P trend < .001). High dietary insulin index was also associated with worse DFS (highest vs lowest quintile, HR = 1.75, 95% CI = 1.22 to 2.51, P trend = .01). The association between higher dietary insulin load and worse DFS differed by body mass index and was strongest among patients with obesity (HR = 3.66, 95% CI = 1.88 to 7.12, P interaction = .04). The influence of dietary insulin load on cancer outcomes did not differ by mutation status of KRAS, BRAF, PIK3CA, TP53, or microsatellite instability. Conclusions: Patients with resected stage III colon cancer who consumed a high-insulinogenic diet were at increased risk of recurrence and mortality. These findings support the importance of dietary management following resection of colon cancer, and future research into underlying mechanisms of action is warranted.